Molecular Identification of Brucella Abortus Bv5 and Strain 19 in Water Buffaloes (Bubalus Bubalis) in Northeast Argentina - Martinez, Diana (2014)
Buffalo (Bubalus bubalis) populations are spread across northern Argentina, and they share their habitat with bovines. Both species are susceptible to brucellosis, and they are under a National Plan of Control and Eradication. To characterize the Brucella spp. that infects buffaloes, the blood of 35 animals that tested positive to brucellosis by a complement fixation test was collected. DNA was obtained and analyzed by polymerase chain reaction using different molecular markers. The genera, species, and biovars of Brucella were established by analyzing specific regions of the genes omp31, eri, alkB, and omp2ab. Brucella spp. was identified in 15 of 35 tested buffaloes. The product of the omp31 gene identified the genera. The detection of two fragments of 297 bp and/or 1000 bp from the eri gene confirmed the presence of B. abortus S19 and wild-type B. abortus. The amplification of the alkB gene allowed the identification of B. abortus biovars characterized by fragments of 498 bp (bv1, bv2, or bv4). The simultaneous amplification of 498 bp (alkB) and 1000 bp (eri) products suggested the presence of B. abortus bv1, which is highly prevalent in the cattle of Argentina. Fragments of 827 bp and 857 bp were amplified from the omp2ab gene, and their sequences showed 100% identity with B. melitensis and B. abortus bv5 (GenBank). However, the 721 bp product (alkB) specific for B. melitensis could not be amplified. This is the first report indicating the presence of B. abortus bv5 in Latin America.